Análisis, diseño e implementación de un sistema web gestor de procesos administrativos realizados en el departamento de consejería estudiantil del Colegio Kleber Franco Cruz, bajo el lenguaje de programación C# utilizando la plataforma de desarrollo libre Mono, la metodología Adaptive Software Development y el gestor de base de datos Postgres. - Núñez Barrera, Wilson Alexander (2015)
It should be mentioned that at present, for an academic institution to become a leader of education, it must be open to technology and computer leaving aside what is considered traditional, not forgetting a very important and indispensable feature in any educational institution , vocational guidance is provided to students. Applications (software) are valuable tools that allow any establishment to achieve the previously mentioned characteristics. For these reasons was evaluated as carrying out activities within the department of student counseling (DCE) school Kleber Franco Cruz, after analyzing the results achieved detect various shortcomings which seriously affected the stored information for this and other reasons He proposed the development and implementation of a web system to help manage administrative activities carried out in the DCE. reservation and organization of psychological appointments, students psychological evaluations, generating statistics psychological test, psychoeducational chips, among other operations: system by implementing the following processes are automated. When developing the system it took into account that it should be accessible from anywhere so we chose ASP.Net with the programming language C #, although some public institutions are required to use free software, that is why the Xamarin Studio tool for application development in C # language and is obtained as a result an open source application that can be hosted on XSP (Linux) or IIS (Windows) servers are used. To store the application information and provide the necessary security chose to use the manager PostgreSQL database, which apart from being an open source DBMS, has features that make it a robust database manager data. The development of this system was made in a volatile and changing environment, for this reason the agile development methodology Adaptive Software Development (ASD), software was implemented this methodology is appropriate to develop systems in environments where requirements live in constant modifications, ASD easily adapts to changes without the result suffers a big impact. It is concluded previously stated that implementation of the system for managing administrative processes was the most feasible to correct errors found in the DCE College Kleber Cruz Franco solution.